Acupuncture at Tiaokou (ST38) for Shoulder Adhesive Capsulitis: What Strengths Does It Have? A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (22nd April 2018) - Yang, Chao; Lv, TaoTao; Yu, TianYuan; Wong, Steven; Lu, MengQian; Li, YiZhen
Abstract : Objective . Tiaokou (ST38) is used as a crucial distal acupoint for treating shoulder adhesive capsulitis (SAC) in traditional Chinese medicine. The objective of this study was to assess the effectiveness and safety of acupuncture at Tiaokou for treating SAC. Methods . We searched eight electronic databases without language restrictions. All the literature was processed to identify RCTs comparing acupuncture at Tiaokou with other therapies (e.g., acupuncture at local shoulder acupoints and nonsteroidal anti-inflammatory drugs). Two reviewers extracted trials and collected outcome data independently. A meta-analysis was performed following a strict methodology. Results . 19 RCTs involving 1944 participants met our inclusion criteria. The majority of the trials were determined to be of low quality. Positive results were found for acupuncture treatment at Tiaokou (as sole treatment or in combination with shoulder acupoints), which resulted in an improved percentage of clinical effectiveness and Constant-Murley Score values, as well as a reduction in Visual Analogue Scale values of SAC patients. Conclusion . Our review found encouraging evidence for the effectiveness of acupuncture at Tiaokou for SAC. Nonetheless, despite stringent methodological analyses, these results need to be strengthened by additional RCTs of higher quality.